2019
DOI: 10.1002/2211-5463.12703
|View full text |Cite
|
Sign up to set email alerts
|

Cellular calcification induced by inorganic polyphosphate involves ATP depletion and opening of the mitochondrial permeability transition pore (mPTP)

Abstract: Inorganic polyphosphate (polyP) is a linear polymer containing tens to hundreds of orthophosphate residues linked by high‐energy phosphoanhydride bonds. PolyP promotes osteocalcification and bone mineralization in both mouse and human osteoblastic cells. In the present study, we examined the molecular mechanism by which polyP affects mitochondrial metabolism to promote cellular calcification in MC 3T3‐E1 osteoblastic cells. The cellular content of adenosine triphosphate ( ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…This phenomenon was consistent with the T98G cell line used in this study (Fig. 1B ), and it also aligned with the findings of our previous study involving the same cell line [ 29 ]. In fibroblast‐derived cell lines, polyP promotes cell proliferation by modulating the activity of basic fibroblast growth factor (FGF‐2) [ 25 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This phenomenon was consistent with the T98G cell line used in this study (Fig. 1B ), and it also aligned with the findings of our previous study involving the same cell line [ 29 ]. In fibroblast‐derived cell lines, polyP promotes cell proliferation by modulating the activity of basic fibroblast growth factor (FGF‐2) [ 25 ].…”
Section: Resultssupporting
confidence: 93%
“…The variations in ATP levels among different cell types can be attributed to the varying amounts of endogenous ATP present in each cell type. ATP depletion in polyP-treated cells has also been reported in a previous study involving the mouse osteoblastic cell line MC3T3-E1 [29]. Our findings indicate that while pyruvate serves as a substrate in cellular energy metabolism and can contribute to ATP production, there are situations where pyruvate may not effectively restore ATP levels in cancer cells.…”
Section: Atp Content In Polyp-treated Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…171 Recently, it has been reported that a decrease of mitochondrial membrane potential by opening mPTP pores is associated with a rise in calcification of polyP-treated MC3T3-E1 osteoblastic cells. 172…”
Section: Physiological Roles Of Polypmentioning
confidence: 99%
“…Interestingly, polyP has also been found to be an modulator (activator) of mTORC1 (target of rapamycin complex 1), a complex that acts as an intracellular homeostatic ATP sensor by activating a series of anabolic metabolic pathways . Recently, it has been reported that a decrease of mitochondrial membrane potential by opening mPTP pores is associated with a rise in calcification of polyP-treated MC3T3-E1 osteoblastic cells …”
Section: Physiological Roles Of Polypmentioning
confidence: 99%